ASSESSMENT OF PHYSICOCHEMICAL PARAMETERS AND HEAVY METALS IN EFFLUENTS FROM ODOGUNYAN INDUSTRIAL ESTATE, LAGOS, NIGERIA - Owalude, S. O.; Odebunmi, E. O.; Babalola, K. O. (FUDMA JOURNAL OF SCIENCES, 2021)
The impact of the industrial effluents from Odogunyan industrial estate on the environment was assessed by determination of some physicochemical characteristics of the effluent samples and comparison with discharged standards to ascertain the efficiency of industries’ wastewater treatment process. The physicochemical parameters were evaluated by conventional methods while heavy metals in the effluent samples were analyzed using Atomic Absorption Spectrophotometer (AAS). The results for all the effluents revealed that temperature was in the range of 32- 35 ; Biochemical Oxygen Demand (BOD) 43-86.7 mg/L; Chemical Oxygen Demand (COD) 492-888 mg/L; Total Dissolved Solids (TDS) 1667-13333 mg/L; Total Suspended Solids (TSS) 350-1000 mg/L; Total Solids (TS) 3350-14333 mg/L; Electrical Conductivity 166.5-12390 μS/cm; Total Acidity (TA) 12-60 mg/L and total hardness 24-56 mg/L. The AAS analysis results showed the average metal levels in mg/L as 0.7-1.15, 0.05-0.44, 2.0-45.0, 0.01 and 0.03-0.17 for Zn, Cu, Fe, Cd and Cr respectively. Thus, there is a need for proper remedial measures of the effluents before their discharge into the water bodies